Group Dynamics in Mathematics Education: Homogeneous Vs. Heterogeneous Group Effects on Problem-Solving Skills - Trisna Jayantika, I Gusti Agung Ngurah; I Putu Ade Andre Payadnya; I Putu Pasek Suryawan (Jurnal Pedagogi dan Pembelajaran, 2025)
Research on heterogeneous group design in mathematics education and empirical evidence comparing the effectiveness of homogeneous and heterogeneous groups on students' problem-solving abilities (PSA) is still limited. However, PSA is an important competency in mathematics, yet the application of effective group design to develop it remains a challenge. This study addresses this gap by investigating the impact of homogeneous group designs on PSA among high school students in Denpasar. Utilizing a quasi-experimental one-group pretest-posttest design, the research involved 120 students who participated in a series of six instructional sessions with homogeneous grouping. Pretest and post-test data were analyzed using paired sam-ple t-tests to assess changes in PSA, focusing on problem understanding, planning, implementation, and reflection. The results of the data analysis test produced a t-value of -18,839 with p-value of 0.000, which was less than 0.05. The findings revealed a significant improvement in PSA scores with homogeneous groups, suggesting that grouping students by similar ability levels enhances peer interactions and instructional support more effectively than heterogeneous group designs. Teacher and student interviews corroborated these results, highlighting more equitable participation and tailored learning experiences in homogene-ous settings. While this study underscores the benefits of homogeneous grouping in improving problem-solving abilities (PSA), it also identifies the need for integrating diverse instructional media. Future research should examine the impact of various educational technologies and broader contexts to refine group design strategies in mathematics education.